The feasibility of the Palestinian movement to implement boycott systems for a state of Zionist occupation: a reading of the results, challenges, and the future of the movement - Jaradat, Mohammad Ahmed (Journal of Humanities & Social Sciences, 2023)
The study aimed to identify Boycott, Divestment and Sanctions Movement (BDS) in terms of its origins and objectives, and the mechanisms of the Palestinian BDS movement’s work. on the general challenges facing the work of the Palestinian Boycott Movement (BDS) at the local, Arab and international levels, After that, an analysis and reading of the future of the (BDS) movement took place, and the study relied on the forward-looking approach in studying the most prominent challenges facing the BDS movement in light of the obstacles it faces on the international scene by some major countries such as the United States of America and the increasing pace of Arab-Israeli normalization. Future scenarios for the movement’s work in light of these challenges. The study concluded with a set of results, the most important of which are: the importance of the boycott movement (BDS) as an effective means of peaceful resistance against the Israeli occupation and the apartheid regime, and the consistency of the principles and objectives of the BDS movement with international laws and principles. To continue achieving achievements and success despite all the obstacles and challenges it faces. The researcher recommended: Work to increase activities and events that raise public awareness of the importance of the movement and its goals, and provide official and popular Palestinian support for that movement.